A monolithic strategy based on an hybrid domain decomposition method for multiphysic problems: Application to poroelasticity - Gosselet, Pierre; Chiaruttini, Vincent; Rey, Christian; Feyel, Frédéric (European Journal of Computational Mechanics, 2004)
A monolithic strategy based on an hybrid domain decomposition method for the numerical simulation of multiphysic problems is presented. It relies on a "physical" choice of primal interface unknowns. First numerical assessments are described for poroelasticity problems.